Long-term outcomes of twins based on the intended mode of delivery*. (18th August 2018) - Fox, Nathan S.; Cohen, Natalie; Odom, Elizabeth; Gupta, Simi; Lam-Rachlin, Jennifer; Saltzman, Daniel H.; Rebarber, Andrei
Abstract: Objective: Recent studies have shown that for twin pregnancies with a cephalic presenting first twin, planned vaginal delivery is not associated with adverse short-term neonatal outcomes, as compared to planned cesarean delivery. Our objective was to compare long-term outcomes in twins, based on planned mode of delivery. Study design: This was a prospective, observational cohort of twin pregnancies delivered by a single MFM practice. All the patients with a twin pregnancy >34 weeks delivered from 2005–2014 were surveyed regarding pediatric outcomes at or after 2 years of life. The survey was mail-based, with phone follow-up for nonresponses or for clarification of answers. Using chi-square, Student's t -tests, and regression analysis we compared outcomes between women who planned a vaginal (with active management of the second stage) versus cesarean delivery. The main outcome measures were: (1) a composite of major adverse outcomes (death, cerebral palsy, necrotizing enterocolitis, chronic renal, heart, or lung disease); (2) a composite of minor adverse outcomes (learning disability, speech therapy, occupational therapy, physical therapy). Results: Five hundred and thirty-two women met inclusion criteria and 354 (66.5%) responded. 178 (50.3%) women planned to have a cesarean delivery (100% of whom had a cesarean delivery) and 176 (49.7%) women planned to have a vaginal delivery (83% of whom had a vaginal delivery). The average age of the children at the time of the survey was 5.9 years. There were no differences in any pediatric outcomes between the two groups. After controlling for maternal age, IVF, obesity, and preeclampsia, the planned mode of delivery was not associated with a composite of major adverse outcomes (aOR 0.673, 95% CI 0.228, 1.985), nor a composite of minor adverse outcomes (aOR 0.767, 95% CI 0.496, 1.188). Conclusions: Planned vaginal delivery with active management of the second stage of labor in twin pregnancies >34 weeks is not associated with adverse childhood outcomes.